Effects of the Geogebra-assisted Missouri mathematics project learning model on students’ mathematical communication ability - Kurniawan, Ilham; Ulfah, Syafika (Jurnal Riset Pendidikan Matematika, 2023)
The purpose of this study was to find the effects of GeoGebra- assisted Missouri Mathematics Project (MMP) learning model on students’ mathematical communication abilities. The study can be categorized as a quantitative experimental research type with a quasy-experimental design. The research population refers to all grade X Physics students of private Senior High School in South Tangerang. The purposive sampling technique was used to a sample size of 38 students as the experiment group and another 34 students as the control group. Data were collected using a descriptive test of mathematical communication ability on the material of the three-variable linear equation system. Further, the t-test was used to analyze the data. Findings showed that the GeoGebra-assisted MMP learning model improves the students mathematical communication abilities at the moderate category.